2014
DOI: 10.3389/fpsyt.2014.00092
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Regulation of Brain Reward Processing with an Emphasis on the Role of CB1 Receptors: A Step Back into the Future

Abstract: Over the last decades, the endocannabinoid system has been implicated in a large variety of functions, including a crucial modulation of brain-reward circuits and the regulation of motivational processes. Importantly, behavioral studies have shown that cannabinoid compounds activate brain reward mechanisms and circuits in a similar manner to other drugs of abuse, such as nicotine, alcohol, cocaine, and heroin, although the conditions under which cannabinoids exert their rewarding effects may be more limited. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 207 publications
(230 reference statements)
0
60
0
Order By: Relevance
“…Endogenous opioids and cannabinoids have been also implicated in drug reward responses, in part through the opioid regulation of the mesolimbic DA pathway (Box 2) and through studies of the role of cannabinoids in adaptations that occur with repeated drug exposures (for reviews, see Covey et al, 2014;Panagis et al, 2014).…”
Section: Box 2 Opioid Regulation Of the Mesolimbic Da Pathwaymentioning
confidence: 98%
“…Endogenous opioids and cannabinoids have been also implicated in drug reward responses, in part through the opioid regulation of the mesolimbic DA pathway (Box 2) and through studies of the role of cannabinoids in adaptations that occur with repeated drug exposures (for reviews, see Covey et al, 2014;Panagis et al, 2014).…”
Section: Box 2 Opioid Regulation Of the Mesolimbic Da Pathwaymentioning
confidence: 98%
“…In this context, a considerable amount of studies have been performed in order to elucidate the effects of cannabinoids (natural or synthetics) in the development of mental alterations, such as addiction, cognitive deficits, anxiety or psychosis. Importantly, different or opposite behavioral effects have been observed after the administration of Δ 9 -THC or synthetic cannabinoid ligands (Fattore et al, 2003; Panagis et al, 2014; Rubino and Parolaro, 2016). It has been demonstrated that for most G protein-coupled receptors, distinct agonists can differentially regulate several signaling pathways through the same receptor by a selective activation of different intracellular effectors.…”
Section: Introductionmentioning
confidence: 99%
“…202 The CB2 receptors has been shown to modulate ventral tegmental dopamine neuron activity, circuitry considered pivotal in the addictive process. 203 …”
Section: Survey Of Current Targets Of Pain Therapeuticsmentioning
confidence: 99%